Men’s Experiences in Feminized Occupations on the Example of Selected Professions - Dudak, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The issues raised in this article concern the functioning of men in feminized professions. The aim of the study was to gather experiences of men working in jobs dominated by women. The research included twenty men and was conducted between February and April 2020 in Poland, using a narrative interview. Research problems were focused on men’s attitudes toward their jobs, the assessment of career advancement opportunities, advantages and disadvantages resulting from working in a feminine environment, relations with colleagues and employers, and reactions of their environment. The interviews revealed a relatively positive image of men’s experiences relating to working with women. The respondents did not notice any specific difficulties in their professions caused by gender stereotypes. They expressed a view that working among women was like any other job. Few difficulties mentioned by the respondents were related mostly to the issue of assistance in activities requiring strength or technical knowledge rather than competences related to a specific profession. Moreover, the interviewees treated their professions as an opportunity for self-development and for gaining experience that they would not have been able to gain in a typically male environment.